Buzzing Sympathetic Nerves: A New Test to Enhance Anisocoria in Horner's Syndrome - Omary, Rawan; Bockisch, Christopher J.; Landau, Klara; Kardon, Randy H.; Weber, Konrad P. (Frontiers in Neurology, 2019)
Introduction Patients with suspected Horner syndrome having equivocal pupil dilation lag and pharmacologic testing may undergo unnecessary MR imaging and work up in the case of false positive pupil test results. Our goal was to increase the diagnostic accuracy of pupillometry by accentuating the inter-ocular asymmetry of sympathetic innervation to the iris dilator with surface electrical stimulation of the median nerve using a standard electromyography machine. We hypothesized that an accentuated difference in sympathetic response between the two eyes would facilitate the diagnosis of Horner syndrome. Methods Eighteen patients with pharmacologically proven Horner syndrome were compared to ten healthy volunteers tested before and after monocular instillation of brimonidine 0.2% to induce pharmacological Horner syndrome. Pupillary responses were measured with binocular pupillometry in response to sympathetic activation by electrical stimulation of the median nerve in darkness and at various times after extinction of a light stimulus. Sudomotor sympathetic responses from the palm were recorded simultaneously. Results In subjects with Horner syndrome and pharmacologically induced unilateral sympathetic deficit, electrical stimulation in combination with the extinction of light greatly enhanced the anisocoria during the evoked pupil dilation, while there was no significant increase in anisocoria in healthy subjects. The asymmetry of the sympathetic response was greatest when the electrical stimulus was given 2s after termination of the light or under constant low light conditions. When given 2s after termination of light, the electrical stimulation increased the mean anisocoria from 1.0mm to 1.2mm in Horner syndrome (p=0.01) compared to 0.22mm to 0.26mm in healthy subjects (p=0.1). In all subjects, the maximal anisocoria induced by the electrical stimulation appeared within a 2s interval after the stimulus. Correspondingly, the largest anisocoria without electrical stimulation was seen between 3-4s after light-off. While stronger triple stimulation further enhanced the anisocoria, it was less well tolerated. Conclusions Electrical sympathetic stimulation 2s after light-off greatly enhances the sensitivity of pupillometry for diagnosing asymmetric pupil dilation due to Horner syndrome. This new method may help to rule in or rule out a questionable Horner syndrome, especially if the results of topical pharmacological testing are inconclusive.